Resource Use Efficiency in Vegetable Production in the Kailali of Sudurpaschim Province - Updhayay, Megh Raj (Journal of NAST College, 2025)
This study aimed to examine factors affecting, resources use efficiency and returns to scale in vegetable production by analyzing impact of resources utilization in Kailali. Applying quantitative causal survey including descriptive research design, it explored impact of resources utilization and socio-economic factors through structured questionnaire from 100 farmers by random sampling. Though, there are extensive researches of agriculture, inputs and returns to scale, very few papers explored in Kailali. Data analysis was carried by frequencies, mean, SD, t-test, Durbin-Watson test and multiple regression model using Cobb-Douglas production function. Indian Vegetables were major responsible for no expected price of vegetables in Dhangadhi Sub-Metropolitan city, Godawari Municipality and Kailari Rural Municipality. This study showed socio-economic factors of farmers played decisive role in resource use efficiency and returns to scale. Education level, extensive service, land, chemical fertilizer and seed were statistically significant to returns from vegetable to farmers whereas subsidy, household size, pesticide and labour could not support to income of farmers. Since efficiency ratio is greater than unity, the resources are underutilized. Chemical fertilizer and pesticide were underutilized and need to increase cost by 10.37% and 72.11% respectively whereas seed and labour were overutilized due to the efficiency ratio is less than unity and need to decrease cost by 14.05 % and 95.88 % respectively for their optimum allocation. Land was underutilized. Lack of training, exposure, education level and extension service were reasons for inefficient use of resources and decreasing returns to scale in production. It is recommended farmers should have technical knowledge for optimizing resources which would increase production and productivity, and increasing returns from vegetable production.